(untitled) (Swiss Medical Weekly, 2017)
PRINCIPLES Optimal management of perforated appendicitis with perityphlitic phlegmon or abscess formation is controversial. The aim of the study was to assess the outcome after a two-step procedure to treat patients with perityphlitic abscess formation. METHODS We retrospectively assessed prospectively collected data from a single-centre database that included adult patients who had appendicitis and perityphlitic abscess (≥3 cm) but no generalised peritonitis, and were treated in 2007–2015. Patients underwent a two-step procedure that comprised antibiotic treatment and drainage when technically feasible (step 1) followed by interval appendectomy (step 2). We evaluated treatment modalities, complications and outcomes. RESULTS Out of a total of 1480 patients with appendicitis, 15 patients presented with perityphlitic abscess. In addition to antibiotic treatment, computed tomography-guided drainage was performed in 12 of these cases. Step 1 and 2 hospital stays were (median, range) 7 days (5–14 days) and 2 days (2–12 days), respectively. One patient’s abscess recurred after 2 months, associated with new onset appendicitis and perforation. Another patient underwent reoperation after interval appendectomy for suspected postoperative peritonitis. CONCLUSION This two-step procedure for appendicitis with appendicular abscess was highly successful (100%) with a low rate of complications (13%). In the view of a potentially increased rate of appendicular neoplasm in combination with abscess formation, the role of interval appendectomy has to be evaluated in larger trials.